MANAJEMEN KOMUNIKASI DALAM MENGELOLA DOVERSITY DI PERUSAHAAN MULTINASIONAL PT. MAERSK - Yazid, Tantri Puspita; Sari Hutagalung, Maduma Yanti; Rumyeni (Departemen Ilmu Komunikasi Universitas Andalas, 2024)
Maersk highly values and respects diversity as its core value, and it is its fundamental responsibility to never discriminate against employees. Discrimination could hinder someone from working or creating things to develop themselves, constructing inequalities and imbalance and a less prosperous society. According to the data from Maersk company, it has a target for >40% women in management (specific targets by level) and >30% diverse nationality of the executive. Maersk company had set a new target for 2025. This research focuses on how Maersk management manages the communication between diversity that exists within, such as culture, age, religion, and different perspectives. This is qualitative research, The informants interviewed were selected through purposive technique, Miles and Huberman model data analysis techniques were used. The results of this study show that PT Maersk manages diversity well through three stages, namely planning, implementation, and evaluation.